Edwards Intuity Elite In a Patient With Bicuspid Aortic Stenosis and Ventricular Septal Defect - Attilio Cotroneo; Gian Luca Martinelli; Gabriele Musica; Mario Bobbio; Marco Diena (International Journal of Cardiovascular Practice, 2017)
This study reports on 65-year-old male with a bicuspid Aortic Stenosis (AS) low flow, low gradient and a congenital Ventricular Septal Defect (VSD) of pars membranosa. A ministernotomy and Cardiopulmonary Bypass (CPB) by aorto-femoral cannulation was performed. The VSD was below the commissure between right and non coronary sinus. It was decided to correct it by a stitch with a pericardial patch and a further safer coverage by the stent of an Intuity Elite aortic valve. To the best of our knowledge this was the first time that a VSD could be covered with a suturless valve for two reasons: International Journal of e and conformable configuration of the valve.